Stem Cell Mobilization with G-CSF versus Cyclophosphamide plus G-CSF in Mexican Children - José Eugenio Vázquez Meraz; José Arellano-Galindo; Armando Martínez Avalos; Emma Mendoza-García; Elva Jiménez-Hernández (Stem Cells International)
Fifty-six aphaereses were performed in 23 pediatric patients with malignant hematological and solid tumors, following three different protocols for PBPC mobilization and distributed as follows: A: seventeen mobilized with 4 g/m2 of cyclophosphamide (CFA) and 10 μg/kg/day of granulocyte colony stimulating factor (G-CSF), B: nineteen with CFA + G-CSF, and C: twenty only with G-CSF when the WBC count exceeded 10 × 109/L. The average number of MNC/kg body weight (BW)/aphaeresis was 0.4 × 108 (0.1–1.4), 2.25 × 108 (0.56–6.28), and 1.02 × 108 (0.34–2.5) whereas the average number of CD34+ cells/kg BW/aphaeresis was 0.18 × 106/kg (0.09–0.34), 1.04 × 106 (0.19–9.3), and 0.59 × 106 (0.17–0.87) and the count of CFU/kg BW/aphaeresis was 1.11 × 105 (0.31–2.12), 1.16 × 105 (0.64–2.97), and 1.12 × 105 (0.3–6.63) in groups A, B, and C, respectively. The collection was better in group B versus group A (p=0.007 and p=0.05, resp.) and in group C versus group A (p=0.08 and p=0.05, resp.). The collection of PBPCs was more effective in the group mobilized with CFM + G-CSF when the WBC exceeded 10 × 103/μL in terms of MNC and CD34+ cells and there was no toxicity of the chemotherapy.